An Exploratory Study of the Effectiveness of Memory Aids for Older People Living in Supported Accommodation. (December 2014) - Collerton, Daniel; Forster, Emily; Packham, Derek
There is increasing evidence that electronic and other aids can support older people's memory. In an effectiveness study, we explored whether assistive technologies could benefit 200 potential beneficiaries in a naturalistic setting. We first interviewed 50 participants to assess needs and preferences for memory aids, then researched, developed and trialled specific aids, and finally administered a follow-up questionnaire assessing future use of aids. Matching aids to needs was not easy. Relatively few people were interested in trailing aids. Simpler aids were most successful. Participants were curious about electronic aids, but found them too complicated and not adapted enough to their needs. Assistance from other people was necessary to prompt use of all types of aids. Future effectiveness studies should focus on longer trials with greater training and support for participants, a wider range of technologies, and more promotion of possible benefits.